The Anxiety of Influence between the Two Poems of Abu Dhu’ayb al-Hazli and Saada Al-Juhaniya - Hassanein, Mohamed Mostufe Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to (1) reexamine Abu Dhu’ayb al-Hazli's "Ayniyyah," a landmark in Arabic poetics, and (2) analyze its intertextual relationships, particularly with Saada's "Ayniyyah." The analysis explores the alignment, contrasts, and transformations between these works and other influential poems. Methods: Using an analytical approach grounded in Harold Bloom’s Anxiety of Influence and misreading theories, the study examines the complex literary connections between Abu Dhu’ayb’s work, Saada’s, and other antecedent texts. Bloom’s framework enables a nuanced exploration of how poetic traditions evolve and how literary uniqueness emerges through these influences. Results: The Anxiety of Influence reveals two core elements: an adaptation of the poetic voice and a shift from feminine lament to masculine resilience, reflecting a reinterpretation of Saada's poem as incomplete. Abu Dhu’ayb’s poem thus serves as a “completion,” integrating earlier styles and conventions to solidify the unique qualities of the al-Hazli elegy. Conclusion: The Anxiety of Influence is pivotal in Arabic poetry, especially among Mukhadram poets. Early Islamic-era poetry often navigates between new expressions and pre-Islamic traditions, echoing the voices of past poets and marking a crucial literary evolution.